2022
DOI: 10.3390/jof8060608
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Succession and Seasonal Variation of Phylloplane Mycoflora of Leucaena leucocephala in Relation to Its Leaf Litter Decomposition

Abstract: To address international food security concerns and sustain a growing global population, global agricultural output needs to increase by 70% by the year 2050. Current agricultural techniques to increase crop yields, specifically the application of chemicals, have resulted in a wide range of negative impacts on the environment and human health. The maintenance of good quality soil organic matter, a key concern in tropical countries such as India, requires a steady input of organic residues to maintain soil fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The study also highlighted the importance of monitoring the fungal colonization of L. leucocephala leaves during the decomposition process, to identify the fungal species responsible for decomposition and understand the dynamics of nutrient cycling in the soil. Moreover, the study found that wet seasons had more fungi on average than dry seasons [19].…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The study also highlighted the importance of monitoring the fungal colonization of L. leucocephala leaves during the decomposition process, to identify the fungal species responsible for decomposition and understand the dynamics of nutrient cycling in the soil. Moreover, the study found that wet seasons had more fungi on average than dry seasons [19].…”
mentioning
confidence: 90%
“…The study established by Gulati et al [19] investigated the potential use of Leucaena leucocephala leaves as green manure, and identified the fungal species responsible for their decomposition. The study was motivated by the necessity to increase global agricultural output by 70% by the year 2050, to address international food security concerns, while also addressing the negative impacts of current agricultural techniques on the environment and human health.…”
mentioning
confidence: 99%
“…Perennial legumes, in addition to providing nitrogen to the coconut palm, increase the content of organic matter and protect the soil against erosion (Mukhametovet al, 2021). The use of species such as Leucaenaleucocephala (Gulati et al, 2022), Gliricidiasepium (Kabaet al, 2019), Clitoriaternatea (Hamza, 2021) and Mucunapruriens (Rugareet al, 2020) var. utilis, are good alternatives as green manures in regions with dry periods since, due to their pivoting root system, they exert less competition with the coconut palm.…”
mentioning
confidence: 99%